2007
DOI: 10.1093/ije/dyl254
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a comprehensive health assessment programme for Australian adults with intellectual disability: a cluster randomized trial

Abstract: The Comprehensive Health Assessment Program (CHAP) produced a substantial increase in GPs' attention to the health needs of adults with intellectual disability with concomitantly more disease detection. The presumption that these will yield longer-term health benefits, while suggestive, remains unexamined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
205
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(217 citation statements)
references
References 19 publications
11
205
0
1
Order By: Relevance
“…The higher-quality studies clearly demonstrated that health checks led to the improved detection of new health problems, with one randomised controlled trial reporting a 60% increase in the diagnosis of new problems and a matched controlled study reporting 2.54 additional health problems identified, on average, in people receiving health checks. 31,32 These studies also reported an increase in the uptake of preventative interventions such as vaccination, cancer screening and sensory testing. These conclusions are also supported by the larger number of uncontrolled studies.…”
Section: Evidence Base For Annual Health Checksmentioning
confidence: 98%
“…The higher-quality studies clearly demonstrated that health checks led to the improved detection of new health problems, with one randomised controlled trial reporting a 60% increase in the diagnosis of new problems and a matched controlled study reporting 2.54 additional health problems identified, on average, in people receiving health checks. 31,32 These studies also reported an increase in the uptake of preventative interventions such as vaccination, cancer screening and sensory testing. These conclusions are also supported by the larger number of uncontrolled studies.…”
Section: Evidence Base For Annual Health Checksmentioning
confidence: 98%
“…20,22 These noted a non-significant trend towards new disease detection after 1 year, but they did not report the extent to which needs had been met or obtain data about health monitoring needs. Unlike our trial, they showed an increase in health-promotion activity, especially with testing of vision and hearing, giving tetanus boosters, and checking hepatitis B serology; in our trial the nurses enquired about vision difficulties and testing, then directed people towards an optometrist, rather than directly testing vision, and the health check did not include hepatitis B serology, so data are not similar.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian trial randomly assigned 453 adults receiving paid support from one provider, into 34 clusters. 20 Improvements in health promotions (eg, sensory impairment testing, immunisations, and cervical screening) were noted in the GP-delivered health-check intervention group 1 year later, but no significant difference in newly detected diseases was noted (p=0.07). 20 This intervention was also inexpensive.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been shown that comprehensive health checks in adults with learning disability, done correctly, identify hidden morbidity 8 and could double the number of their health needs addressed, compared with standard GP care. 9,10 Those patients with moderate, severe and profound learning disabilities are known to have over twice the number of clinical conditions found in their non-disabled peers. 11 In a study last year the level of new need revealed by repeated checks, even at the shortest interval (mean 14 months), was as high as that at initial check, which suggests the optimum interval between checks may well be 1 year.…”
mentioning
confidence: 99%